Improving Physical Fitness through a Circuit Games Model - Maghfirah, Dina Amaliyah El; Junaidi, Ilham Arvan; Lanos, Muhsana El Cintami (PPSDP International Journal of Education, 2024)
This study aims to determine how effectively these circuit games can enhance physical fitness among young students and whether this approach can lead to measurable improvements in their overall physical health and capabilities. This study employs the action research method to assess the impact of circuit games on improving student fitness. By observing changes in student behavior and physical capabilities, the researcher aims to determine the effectiveness of the circuit game model in enhancing overall fitness. The TKSI (Test Kebugaran Siswa Indonesia) is used as a key tool to measure and evaluate the students’ fitness levels throughout the study. Through this approach, the study seeks to provide insights into how circuit training games can be effectively utilized to boost physical fitness among students. The results stated that physical fitness is a crucial asset for students, as it significantly enhances their ability to perform daily activities and tasks efficiently. Students with good physical fitness are generally better equipped to handle the demands of both academic and extracurricular activities, while those with lower fitness levels often struggle with fatigue and difficulty in daily tasks. Circuit training games offer a dynamic approach to fitness, combining aerobic exercises with strength training and flexibility. These games involve various stations, each designed to target different aspects of physical fitness, and require students to complete each station within a set time before moving on to the next.